"In their own words" : the advocates of European integration - Gill, Christopher (Northants : S.E.K. Publications, 1996)
This book has been meticulously researched and compiled to make available in an accessible form the statements of the advocates of an "ever closer union among the people of Europe".
International Currency Review (Occasional Paper No 7) August, 1996
Includes bibliographical references.
osa 21/09/2016
Loans
Keywords: Economic integration; Economic integration - european union; European Economic Community .; Europe